Variants in linkage disequilibrium with the late cornified envelope gene cluster deletion are associated with susceptibility to psoriatic arthritis - Mc Manus, Ross; Kane, David (My University, 2010)
Objective: A common deletion mapping to the psoriasis susceptibility locus 4 on chromosome 1q21, encompassing two genes of the late cornified envelope (LCE) gene cluster, has been associated with an increased risk of psoriasis vulgaris (PsV). One previous report found no association of the deletion with psoriatic arthritis (PsA), suggesting it may be a specific risk factor for PsV. Given the genetic overlap between PsA and PsV, a study was undertaken to investigate whether single nucleotide polymorphisms (SNPs) mapping to this locus are risk factors for PsA in a UK and Irish population. Methods: Three SNPs with prior evidence of association with susceptibility to PsV were genotyped in 1057 patients with PsA using Sequenom iPlex chemistry and genotype frequencies compared with data available for 5575 healthy controls. Two of the SNPs, rs4112788 and rs4085613, were reported to be highly correlated with the LCE deletion. The third SNP, rs6701216, was previously reported to be associated with PsV in a US population. Results: Alleles tagging the deletion for both rs4112788 and rs4085613 were found to be enriched in cases compared with controls (69% vs 65%) and significantly associated with increased susceptibility to PsA (ptrend = 0.001, OR 1.19 and ptrend = 0.001, OR 1.18, respectively). No association was observed with rs6701216. Conclusions: The evidence presented here supports LCE deletion as a risk factor for PsA in a UK and Irish population. It suggests that this locus is a risk factor within a shared aetiological pathway that contributes to psoriatic skin disease in both PsV and PsA.
PUBLISHED
PMID: 20643763
Keywords: Genetics; psoriasis; Genes & Society